Selected Lectures of the XXIV National Congress of the Italian Society of Neonatology (Società Italiana di Neonatologia, SIN); Rome (Italy); September 26-29, 2018 - - (Hygeia Press di Corridori Marinella, 2018)
Selected Lectures of the XXIV National Congress of the Italian Society of Neonatology (Società Italiana di Neonatologia, SIN); Rome (Italy); September 26-29, 2018 Guest Editor: Mauro Stronati LECT 1. FEEDING INTOLERANCE IN PRETERM INFANTS • A. Aceti LECT 2. PREBIOTICS ARE ALL THE SAME • M. Agosti LECT 3. NURSE AND PAIN MANAGEMENT IN NEWBORN: THEORETICAL AND PRACTICAL ASPECTS • A. Allegro, I. Arenga, S. Lazzari LECT 4. THE "THINKING" NURSE: A RESOURCE OR A TROUBLESOME FIGURE? HOW TO INTERACT WITHIN A MULTIDISCIPLINARY TEAM • M. Altafini, D. Bolognini, P. Coscia LECT 5. COMPARISON OF PAIN MEASUREMENT PERFORMED BY NURSES AND PARENTS • G. Ancora, N. Simeone, E. Baudassi, T. Pesaresi, S. Grandi, F. Fabbri, S. Lazzari LECT 6. RED REFLEX AT BIRTH: AIM, EXECUTION AND IMPLEMENTATION • G. Araimo, S. Aversa, A. Baldascino, S. Frezza LECT 7. ERRORS IN THERAPY ADMINISTRATION IN THE NEONATAL INTENSIVE CARE UNIT: WHICH IS THE BEST STRATEGY TO PREVENT THEM? • M.C. Ariotti, F. Vignali, F. Logrippo, F. De Matteis, M. Luciano, A. Coscia, F. Cresi, E. Bertino LECT 8. KANGAROO MOTHER CARE AT THE HEART OF INDIVIDUALIZED FAMILY-CENTERED CARE: IMPLICATIONS FOR THE DEVELOPMENT OF PRETERM INFANTS • C. Artese, G. Calciolari LECT 9. KANGAROO MOTHER CARE IN ITALY: 2017 SURVEY • C. Artese, G. Paterlini; Neonatal Care Study Group LECT 10. NEWBORN OF MOTHERS AFFECTED BY THYROID DISEASE • G. Barera, M.C. Vigone, G. Vincenzi LECT 11. NURSING RECOMMENDATIONS ON THE SKIN MANAGEMENT OF TERM AND PRETERM INFANT • E. Bernabei, P. Coscia, M. Di Giuseppe, L. Guarinoni, S. Tuccio, V. Vanzi LECT 12. INTRAUTERINE GROWTH RESTRICTION: SHORT AND LONG TERM OUTCOME • E. Bertino, A. Coscia, E. Spada, M. Baricco, S. Sottemano, P. Di Nicola LECT 13. INTERSOCIETY POLICY STATEMENT ON THE USE OF WHOLE-EXOME SEQUENCING IN THE CRITICALLY ILL NEWBORN INFANT • A. Borghesi, M.A. Mencarelli, L. Memo, G.B. Ferrero, A. Bartuli, M. Genuardi, M. Stronati, A. Villani, A. Renieri, G. Corsello, on behalf of their respective Scientific Societies LECT 14. LET'S SHED SOME LIGHT ON DISCHARGE INSTRUCTIONS FOR NEWBORNS • K. Bressan, P. Paolillo LECT 15. STOP-IVH PROTOCOL IN VERY LOW BIRTH WEIGHT INFANTS: A QUALITY IMPROVEMENT APPROACH • L. Brombin, A. Galderisi, E. Baraldi, E. Lolli, D. Trevisanuto LECT 16. MINDFULNESS IN HELP FOR THE OPERATORS IN NICU: AN EXPERIMENTAL TRAINING PATH AT THE S. ANNA TURIN HOSPITAL • G. Cacciato, L. Ostacoli, M. Montanari LECT 17. KANGAROO MOTHER CARE: ITS BIRTH, WORLDWIDE DIFFUSION, SCIENTIFIC EVIDENCE • G. Calciolari LECT 18. USE OF BUNDLES TO PREVENT CENTRAL LINE ASSOCIATED BLOODSTREAM INFECTION IN NEONATAL INTENSIVE CARE UNITS • A. Capasso, D. Celentano, R. Mastroianni, N. Pozzi LECT 19. NEONATE OF MOTHER WITH AUTOIMMUNE DISEASE • L. Capasso, M. Palma, C. Coppola, C. Gagliardo, C. Parrella, S. Cioffi, C. Colinet, F. Raimondi LECT 20. RETINOPATHY OR PREMATURITY: DIAGNOSIS AND THERAPEUTIC APPROACHES BY THE OPHTHALMOLOGIST • S. Capobianco LECT 21. STRATEGIES FOR HUMAN MILK FORTIFICATION • M. Carta, G. Corsello LECT 22. NEONATAL ACUTE KIDNEY INJURY: DIAGNOSIS AND TREATMENT CHALLENGE • D. Cattarelli LECT 23. ROLE OF MILRINONE IN THE MANAGEMENT OF RIGHT VENTRICULAR DYSFUNCTION • R.M. Cerbo LECT 24. MULTIDISCIPLINARY EXPERIENCE WITH A CASE OF OMPHALOPAGUS TWINS • M. Cheli, A. Barletta, M. Colledan, B.G. Locatelli, P. Betalli, L. Migliazza, M. Colusso LECT 25. NEONATAL CRANIAL ULTRASOUND: HOW TO OPTIMIZE ITS PERFORMANCE • A. Chiara LECT 26. A CLINICAL AND DIAGNOSTIC APPROACH TO A NEWBORN WITH MULTIPLE CONGENITAL MALFORMATIONS • P. Cianci, A. D'Ambra, L. Memo LECT 27. BASIC ECHOCARDIOGRAPHY COURSE FOR THE NEONATOLOGIST • I. Corsini, S. Fiocchi, K. Rossi, S. Salvadori, F. Schena, M. Savoia LECT 28. MANAGEMENT OF SHORT BOWEL SYNDROME IN THE NEONATAL POPULATION • L. Corvaglia, S. Martini LECT 29. STRATEGIES OF NUTRITION AND FORTIFICATION IN PRETERM SMALL-FOR-GESTATIONAL AGE OR GROWTH-RESTRICTED NEWBORNS • A. Coscia, M. Baricco LECT 30. THE MUCOPOLYSACCHARIDOSES • S. Costa, C. Cocca, G. Vento LECT 31. FEEDING INTOLERANCE AND GASTROESOPHAGEAL REFLUX • F. Cresi, E. Maggiora LECT 32. FAMILY-CENTERED CARE IN ITALIAN NEONATAL INTENSIVE CARE UNITS: PARENT EXPERIENCE AND SATISFACTION, A SYNTHESIS OF A MULTICENTER STUDY AND PRELIMINARY RESULTS • I. Dall'Oglio, A. Portanova, R. Mascolo, E. Tiozzo, A. Ragni, P. Amadio, O. Gawronski, M. Fiori, A. Dotta, C. Offidani, S. Piga, G. Rocco, R. Alvaro, J.M. Latour; the Italian NICUs Family-Centered Care Study Group LECT 33. RESPIRATORY SUPPORT AND PHARMACOLOGICAL TREATMENT OF BRONCHOPULMONARY DYSPLASIA: TOWARDS INDIVIDUALIZED CARE • C. Dani LECT 34. DECREASING THE POLLUTION OF HUMAN MILK, WHILE DEFENDING THE GOOD REPUTATION OF BREASTFEEDING • R. Davanzo, C. Di Lucca, A. Derosa, C. Mastrorilli, F. Forte, M. Delvecchio, P. Appio, V. Targiani, C. Figliuolo, T. Faillace LECT 35. CAN BLOOD GAS ANALYSIS BY UMBILICAL CORD ARTERY PREDICT CLINICAL OUTCOME IN NEWBORNS WITH APGAR SCORE ≥ 7 AT 5 MINUTES FROM BIRTH? • G. De Bernardo, R. Ippolito, M. Giordano, F. Beccagutti, D. Sordino, P. Villani LECT 36. ULTRASOUND FINDINGS IN NEONATAL MENINGITIS • A. Di Comite LECT 37. CONTAMINANTS IN INFANTS' FOODS • S. Di Fabio, V. Nardi LECT 38. LEFT VENTRICULAR DYSFUNCTION: COULD BE FENOLDOPAM USEFUL? • D. Doni LECT 39. THE NEONATAL NETWORK OF THE ITALIAN SOCIETY OF NEONATOLOGY • A. Fabiano, D. Di Lallo, F. Franco, P. Paolillo LECT 40. VISUAL FUNCTION DEFICIT IN PRETERM NEWBORNS • E. Fazzi, L. Malerba, M. Gnesi, A. Rossi LECT 41. CASE REPORT: SEVERE ACUTE BRONCHIOLITIS • T. Fedeli, F. Cattaneo LECT 42. ACUTE KIDNEY INJURY: DEFINITION AND CLASSIFICATION • R. Galiano, P. Novellino LECT 43. HEALTH-RELATED QUALITY OF LIFE OF FORMERLY PRETERM INFANTS FROM CHILDHOOD TO ADULTHOOD • F. Gallini, D.U. De Rose, H. Hindocha, K. Del Vecchio, M. Coppola, L. Maggio LECT 44. COMPUTERIZED MANAGEMENT OF THE EMERGENCY: FROM THE REQUEST TO THE APPROPRIATE HOSPITALIZATION • M. Gente, F. Franco, D. Di Lallo LECT 45. SEX-RELATED DIFFERENCES IN THE OUTCOME OF PRETERM INFANTS: A REVIEW • P. Ghirri, M. Ciantelli LECT 46. GROWTH ASSESSMENT AND NUTRITION • M.L. Gianni, P. Roggero, F. Mosca LECT 47. BREASTFEEDING GUIDED BY NEWBORN • A. Giustardi, M. Stablum, A. Semjonova LECT 48. TEAMWORK AND ON THE JOB TRAINING IN NEONATAL INTENSIVE CARE UNIT • L. Guarinoni, E. Dioni LECT 49. THE ROLE OF THE NURSE IN THE PROMOTION OF THE KANGAROO MOTHER CARE IN THE NEONATAL INTENSIVE CARE UNIT • G. Ierardi, G. Cuomo, N. Bertoncelli, L. Lucaccioni, E. Garetti, L. Bedetti, F. Ferrari LECT 50. BREASTFEEDING PROMOTION IN NEONATAL INTENSIVE CARE UNIT • L. Ilardi LECT 51. PERINATAL PALLIATIVE CARE IN 2018: A NATIONAL SURVEY • P. Lago, M.E. Cavicchiolo, F. Benini LECT 52. METABOLIC ACIDOSIS IN CONGENITAL HEART DISEASES • S. La Placa LECT 53. RECENT ADVANCES IN BREASTFEEDING • S. Longo, M. Stronati LECT 54. CONJOINED TWINS: NEONATAL MANAGEMENT • G. Mangili, M. D'Angiò, C. Gilardi, M. Giozani, D. Martinelli LECT 55. INTRACAVITARY ECG FOR CENTRAL CATHETER'S TIP LOCATION IN INFANTS • R. Mastroianni, A. Capasso, N. Pozzi, D. Celentano LECT 56. RESPIRATORY VIRUS INFECTIONS IN CHILDREN: PREVENTION AND TREATMENT • P. Mastromarino, E. Schiavi LECT 57. COMMUNICATION, MEDIA, AND MASS-MEDIA: HOW CAN WE GET READY TO DEAL WITH ALL OF THIS? • A. Mattiola, B. Gigantesco, M. Del Pistoia, F. Lorenzoni, P. Ghirri, E. Sigali, S. Bardelli, S. Tognarelli, M. Ciantelli, R. Scaramuzzo, A. Cuttano LECT 58. GENETIC ASSOCIATION WITH CONGENITAL HEART DISEASE • I. Mauro LECT 59. EARLY STRESS AND EPIGENETIC EFFECTS IN PRETERM INFANTS • R. Montirosso, L. Provenzi LECT 60. FOLLOWING UP THE RESPIRATORY CONSEQUENCES OF PRETERM BIRTH • L. Moschino, M.E. Cavicchiolo, E. Baraldi LECT 61. NEONATAL BLEEDING DISORDERS AND PLASMA TRANSFUSION • M. Motta, B. Guaragni, G. Chirico LECT 62. ASSESSMENT OF NURSING SKILLS: THE EXPERIENCE OF A NEONATAL INTENSIVE CARE UNIT • S. Muscolo, L. Plevani LECT 63. EMERGING BIOMARKERS AND METABOLOMICS FOR MANAGING NEONATAL SEPSIS • M. Mussap, V. Fanos LECT 64. ENTERAL FEEDING IN PRETERM INFANTS: NOT AS TRIVIAL AS IT IS SUPPOSED TO BE • A. Orsi, L. Ilardi, A. Coscia, G. Salvatori, F. Cresi LECT 65. KANGAROO MOTHER CARE AND PROMOTION OF BREASTFEEDING: THE BREASTFEEDING WHEEL • S. Perugi LECT 66. NEUROLOGICAL COMPLICATIONS DURING RESPIRATORY SYNCYTIAL VIRUS INFECTION • S. Picone, F.